Liberia : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2005 Article IV Consultation highlights that Liberia's real GDP rebounded in 2004, following a steep decline in the second half of 2003 on account of the hostilities and the imposition of the United Nations ban on timber exports. Prices, particularly of food items, have stabilized as supply constraints eased, and the exchange rate has returned to pre-conflict levels. Official reserves increased modestly from low levels. For 2005, the economic recovery is expected to strengthen, underpinned by continued consolidation of the security situation and reconstruction activities.